Hubungan Aktivitas Fisik dan Kebiasaan Merokok dengan Derajat Hipertensi pada Usia Dewasa : The Relationship of Physical Activity and Smoking Habits with the Severity of Hypertension in Adults - Tommy Wowor; Retno Widowati; Mia Atlantic; Maulana Jundi Farrel (Journal of Nursing Education and Practice, 2026)
Introduction: Hypertension is one of the major health problems among adults and can lead to various complications if not properly controlled. Physical activity and smoking habits are important factors that may influence blood pressure levels and the severity of hypertension. The prevalence of hypertension in Indonesia remains high, reaching approximately 36%, while the Indonesian Basic Health Research reported a prevalence of 34.1%. This condition indicates that hypertension continues to be a significant public health concern requiring effective prevention and control of its risk factors.Objectives: To determine the relationship between physical activity and smoking habits with the degree of hypertension among adults at Ciracas Community Health Center, East Jakarta.Method: This study employed a quantitative research design with an observational analytic approach using a cross-sectional method. A total of 88 adult patients with hypertension were selected through purposive sampling. Data collection was conducted using the latest blood pressure records classified according to the Joint National Committee 7 (JNC 7), the Global Physical Activity Questionnaire (GPAQ) to assess physical activity levels, and the Glover–Nilsson Smoking Behaviour Questionnaire to evaluate smoking habits. Data were analyzed using the Chi-Square test.Result: The results showed that most respondents had moderate physical activity levels (39.8%), did not have smoking habits (70.5%), and experienced stage 1 hypertension (61.4%). Statistical analysis indicated a significant relationship between physical activity and the degree of hypertension (p < 0.05). However, smoking habits were not significantly associated with the degree of hypertension (p > 0.05).Conclution: Physical activity is significantly associated with the degree of hypertension among adults, whereas smoking habits are not significantly related to hypertension severity. Regular physical activity may contribute to better blood pressure control and reduced hypertension severity. Therefore, healthcare professionals, particularly nurses, should strengthen health promotion and preventive programs by providing education and motivation to encourage patients to engage in regular physical activity.